Serious Games as a Method for Enhancing Learning Engagement: Student Perception on Online Higher Education During COVID-19 - Arias-Calderón, Manuel; Castro, Javiera; Gayol, Silvina (Frontiers in Psychology, 2022)
The COVID-19 pandemic has enforced social isolation in many countries worldwide, which forced teachers at all levels of education, including the university context, to adapt new teaching strategies. This study presents a method developed in this regard, that is, serious games were used as a complement to synchronous online classes to ensure the continuity of pedagogical activities in a physiology course at Universidad Andrés Bello, Chile. Using serious games is a strategy in the field of gamification, which is a commonly used learning strategy for online teaching as necessitated by COVID-19. This study is quantitative in nature and conducted a questionnaire survey on 108 second-year undergraduate nursing students to determine their perception about this innovation. The results demonstrate that the students well valued the proposed pedagogical innovative model in terms of motivation and engagement. Moreover, they reported that the model can serve as a meaningful learning experience. These perceptions suggest that the model is an efficient strategy for implementing the physiology curricula in the context of online teaching. Moreover, the results imply that the model should be applied to other courses and disciplines in the undergraduate program and provide support that it is a valid strategy for face-to-face teaching. Lastly, the finding points to the potential of the model to be explored as a learning strategy in the age of education post-COVID-19.